2012
DOI: 10.1159/000336959
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Characteristics of Ocular and Cervical Vestibular Evoked Myogenic Potentials in Intact and Dehiscent Ears

Abstract: Cervical and ocular vestibular evoked myogenic potentials (cVEMPs and oVEMPs) to air-conducted tone bursts (250–2000 Hz) were recorded in 14 patients with superior canal dehiscence (SCD) and 32 healthy controls. For cVEMPs, the most common ‘optimal frequency’ in control ears (48.2%) was 500 Hz; for oVEMPs, it was 1000 Hz (51.8%). We found a significant interaction between age and frequency, with a shift towards higher-frequency tuning in older subjects. cVEMP and oVEMP tuning in SCD was characterised by a broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 72 publications
(43 reference statements)
5
59
1
1
Order By: Relevance
“…Similar findings are also reported for oVEMP responses in healthy subjects [Chihara et al, 2009;Murnane et al, 2011]. However, it is reported that 500 Hz is not always the best stimulation frequency; for some subjects, 750 or 1,000 Hz might be optimal [Piker et al, 2013;Taylor et al, 2012]. The effect of stimulus frequency on the amplitude of cVEMP responses varies with age, with young adults giving peak amplitudes at 750 Hz, while older adults required 1,000-Hz stimulation [Piker et al, 2013].…”
Section: Discussionsupporting
confidence: 80%
“…Similar findings are also reported for oVEMP responses in healthy subjects [Chihara et al, 2009;Murnane et al, 2011]. However, it is reported that 500 Hz is not always the best stimulation frequency; for some subjects, 750 or 1,000 Hz might be optimal [Piker et al, 2013;Taylor et al, 2012]. The effect of stimulus frequency on the amplitude of cVEMP responses varies with age, with young adults giving peak amplitudes at 750 Hz, while older adults required 1,000-Hz stimulation [Piker et al, 2013].…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies indicated that threshold was more valuable than peak-to-peak amplitude in distinguishing healthy from pathological ears in both SCD and Mé-nière's disease [Brantberg et al, 1999;Rauch et al, 2004;Taylor et al, 2012]. Thresholds, however, overlap between the SCD and healthy populations, and threshold measurement can be time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…34 Of patients and controls aged .40 years, 93.8% had corrected amplitude values greater than the mean 12 SD of the control group. However, neither the sensitivity nor the specificity could be determined in this subset.…”
Section: 32mentioning
confidence: 87%
“…There were 9 Class III studies. 24,25,[28][29][30][31][32][33][34] A meta-analysis was considered but not performed given the heterogeneity of the studies.…”
mentioning
confidence: 99%